An RRAM retention prediction framework using a convolutional neural network based on relaxation behavior. Issue 1 (1st March 2023) - Zhang, Yibei; Zhang, Qingtian; Qin, Qi; Zhang, Wenbin; Xi, Yue; Jiang, Zhixing; Tang, Jianshi; Gao, Bin; Qian, He; Wu, Huaqiang
Abstract: The long-time retention issue of resistive random access memory (RRAM) brings a great challenge in the performance maintenance of large-scale RRAM-based computation-in-memory (CIM) systems. The periodic update is a feasible method to compensate for the accuracy loss caused by retention degradation, especially in demanding high-accuracy applications. In this paper, we propose a selective refresh strategy to reduce the updating cost by predicting the devices' retention behavior. A convolutional neural network-based retention prediction framework is developed. The framework can determine whether an RRAM device has poor retention that needs to be updated according to its short-time relaxation behavior. By reprogramming these few selected devices, the method can recover the accuracy of the RRAM-based CIM system effectively. This work provides a valuable retention coping strategy with low time and energy costs and new insights for analyzing the physical connection between the relaxation and retention behavior of the RRAM device.